Prognostic Factors for the Therapeutic Performance of Cisplatin in Head and Neck Malignancies - Jungbauer, Frederic; Huber, Lena; Ludwig, Sonja; Rotter, Nicole; Walter, Beatrice; Zaubitzer, Lena; Lammert, Anne (Frontiers in Oncology, 2022)
Introduction: For squamous cell carcinoma of the head and neck (HNSCC), cisplatin is used as primary or adjuvant (radio)chemotherapy. In terms of dosage, two main regimens are used, weekly 40mg/m2 or 3-weekly 100mg/m2. For an optimal outcome, the highest possible cumulative total dose of cisplatin is aimed for. The selection of the scheme is patient-specific, but the factors for the selection of the optimal scheme have not yet been conclusively researched. The aim of this study was to find correlations between initial laboratory values and the cumulative total dose of cisplatin, as well as any correlations between early laboratory values or their dynamics and later laboratory values or their dynamics to provide support in the selection of the chemo regimen. Material and methods: In this retrospective study, the clinical data and laboratory values, namely glomerular filtration rate (GFR), hemoglobin, albumin, leucocyte, erythrocyte and platelet count, over the course of time of 79 patients with HNSCC who had received chemotherapy with cisplatin in our clinic between 2018 and 2021 were evaluated. Results: Patients on 3-weekly regimens achieved a higher mean cumulative total dose of cisplatin than patients on weekly regimens (214.18±65.95 vs 183.33±65.2 mg/m2). Significant positive correlations were seen for total cumulative dose of cisplatin with initial GFR (p=0.001, Pearson's r=0.364), initial hemoglobin (p=0.035, r=0.237), initial erythrocyte (p=0.002, r=0.337), and initial albumin (p=0.002, r=0.337). There were no significant correlations for initial leucocyte or platelets. Regarding the dynamics of the laboratory values under the first chemo administration, no correlation was found with later laboratory values or dynamics. Discussion: As in other prospective studies, our retrospective analysis found a higher cumulative total dose in the 3-weekly regimen. As this seems to correlate positively with patient outcome, superiority of the 3-weekly regimen over the weekly regimen can be assumed. Functioning organ systems, especially of the bone marrow and kidneys, are associated with an increased cumulative total dose and can therefore be regarded as predictive factors. Regular monitoring of laboratory values is nevertheless essential throughout the entire course of chemotherapy.